An Investigation of the Factors Influencing the Utilization of E-Wallets in Higher Learning Institutions in Zambia Using Technology Acceptance Model - Moonde, Chimuka; Phiri, Jackson (Zambia ICT Journal, 2021)
This study looked into the factors that influence the use of e-wallets in Zambian higher learning institutions. Based on the Technology Acceptability Model, this study presented an e-wallet acceptance model. Perceived ease of use, perceived utility, gender, perceived cost and perceived risk were all investigated as potential predictive variables. The Likelihood Ratio Test was utilized in this study, and the results showed that perceived ease of use and gender had a significant impact on students’ use of e-wallets, whereas perceived usefulness, perceived cost and perceived risk had no effect. Perceived usefulness, on the other hand, came quite close. As a result, software developers that create e-wallets for students should make them as simple as possible to use. Additionally, e-wallet software developers should take into account preferences that appeal to each gender differently, as gender influences students’ desire to use e-wallets.